Investigating the Contributing Factors of Continuance Use of Smart Meter in Melaka - Abdullah A.; Yusoff N.S.; Abdul Latif N.W.; Zahari A.R.; Kaman Z.K.; Ismail Z.; Wan Mohamad Norafi W.H. (Springer Science and Business Media Deutschland GmbH, 2023)
Acceptance; Continuance use; Contributing factor; Government IS; Locus of causality; Malaysian governments; Malaysians; Perceived ease-of-use; Perceived usefulness; Smart meters